The Renaissance literature of Crete and Cyprus: looking back over forty years. (4th April 2016) - Holton, David
Abstract : My subject is the relatively small body of literary texts written on the islands of Crete and Cyprus, during the sixteenth and seventeenth centuries, under the influence of the Italian Renaissance. As a matter of fact, the two articles I published in BMGS during the first ten years of its existence had nothing to do with Renaissance literature. My delayed appearance in my chosen field offers me a personal angle to comment on one of the ways the subject has changed since the mid-1970s.